PENGARUH HUMAN CAPITAL DAN GENDER TERHADAP KUALITAS AUDITOR PADA KANTOR AKUNTAN PUBLIK DI INDONESIA - Fahmi Ahmad Riyadi; Endang Kiswara (Diponegoro Journal of Accounting, 2015)
Human capital is the most important asset of Public Accounting Firms. A Public Accounting Firm must make sure they have enough personnel equipped with the required competencies and professional characteristics so that they may perform in accordance with the standards, legal requirements, and expectations of the public. And now, the number of woman auditor is increasing. Not only be a junior auditor but also the manager even partner in Public Accounting Firm. This research examines the effect of human capital and gender on auditor quality in Indonesian Public Accounting Firm. Samples are 66 auditor which was obtained from Public Accounting Firms. The result indicate that human capital affect the auditor quality in Indonesia Public Accounting Firm. While gender doesn’t affect the auditor quality. In addition, in comparing the effect of human capital on the quality auditors, foreign Public Accounting Firm (KAPA) has a greater influence than national Public Accounting Firm (KAP).